Kesiapan psikologis santri baru di era pandemi Covid-19 di Ponpes Darul Ulum Jombang - Retnowuni, Arifa; yani, athi linda (Borobudur Nursing Review, 2021)
New santri (student) at pondok pesantren (Islamic boarding school) usually those who enter the stage of adolescent development as it is known at the age of adolescence is a period of transition and major changes occur both physically, psychologically and relationships in the social environment. Santri are just starting to learn to adapt to a new environment, new atmosphere and of course all will have foreign feelings with changes in physical, psychological, social and cultural conditions. The adjustment of new santri is very much needed so that they can follow the culture and rules of the school. The inability to adapt can lead to various unwanted social problems, such as conflict or disruption of communication relationships. This can cause individuals to face difficulties and frustrations so that individuals was far from feeling happy, comfortable and safe in the environment where they live. New santri who experience psychological problems must immediately receive appropriate treatment so as to prevent unwanted physical and mental health problems such as depression, impaired self-concept and other physical problems. Based on the description above, the aim of the research was to find out the psychological condition of the new santri while living in the school. This study used a survey to obtain the data of the psychological condition of the new santri. The research was conducted in male and female dormitories. The sample in this study were all new santri living in the dormitory. The sampling technique used was the total sample method. In this study, the instrument used by using a questionnaire consists of 14 questions related to the psychological condition of the new santri. The results of the study showed that many students who did not feel comfortable living in the dormitory, on average they experienced anxiety disorders and stress about their new environment.